Perancangan Novel Grafis Para Tokoh Punakawan Sebagai Bentuk Pelestarian Kisah Pewayangan - Wangga, Ryan Aristo; Tjandra, Miki; Aryani, Dewi Isma (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2025)
Wayang legends are among the numerous aspects of Indonesian culture that are gradually being forgotten. One illustration is the Punakawan tale, which is significant in promoting moral principles and forming societal norms. The goal of this design is to encourage young people, both artists and the general public, to get interested in local culture. In order for local culture to survive through artistic creations that are current and captivating to the younger generation, it is hoped that artists will be motivated to study and investigate Indonesia's rich cultural heritage. This quantitative study employs the glass box technique approach with the goal of educating the next generation about the morals of Punakawan characters. A graphic novel book about the Punakawan narrative, which has been altered and infused with fantasy elements, is the outcome of this research. Combining narrative and illustration is a visual communication method that reinforces character qualities and makes reading more appealing to younger generations. It is anticipated that this strategy will make the Punakawan story more palatable and acceptable to Indonesia's youth of today, allowing it to be used as a character teaching tool.